A Method for Assessing Shoreline Stability of Alpine Lake, West Virginia. (April 2017) - Rando, Carolina; Hopkinson, Leslie; O'Neal, Melissa; Fillhart, Jason
Abstract: Rapid stability assessments are tools commonly applied to stream reaches to evaluate potential for instability and are often used to prioritize management strategies. In this work, a rapid stability assessment was created to evaluate the stability of the shoreline of Alpine Lake in West Virginia, USA. First, the assessment tool was created considering the metrics of bank height, bank angle, erosion, armoring, wind and wave action, unconsolidated materials, protection measures, vegetation, and accretion. The resulting tool was applied to 83 reaches (20–100 m in length) of the lake shoreline. The reaches were rated in terms of potential instability: very low (14%), low (42%), moderate (33%), high (10%), and very high (1%). Second, erosion rates were monitored at eight locations using erosion pins. Average erosion rates up to 0.22 mm/d were observed. Measured erosion rates generally supported the rapid assessment results, but there were some exceptions. Additional categories that consider human activity along the lakeshore for recreation should be added. If used without continued erosion monitoring, the rapid assessment should be completed multiple times because the stability of the banks with little vegetation buffer varied by season. Lastly, reclamation strategies are discussed.